Peranan Kepemimpinan Guru Pendidikan Agama Kristen Ditinjau dari Katekismus Heidelberg Minggu Ke-12 dalam Meningkatkan Minat Belajar Siswa di SD Negeri Pakupetas Kelas 4 Semester Genap Tahun Pelajaran 2020/2021 - Dominggus Umbu Dingu; Elisabeth Dethan; Prihadi Kristiyan; Petrus Kefas Loka (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2023)
In the research, the author found several things that happened, including: how the role of the Religious Education Teacher as a leader in terms of the Heidelberg Catechism week 12 affects students' interest in learning. And how big is Teacher Pak as a Leader in terms of the Heidelberg Catechism week 12 towards students' interest in learning? The aim is to find out the role of Teachers as Leadership in terms of the Heidelberg Catechism week 12 towards students' interest in learning, to find out how big the role of Teachers as Leadership is as a leader. Leadership is reviewed from the 12th week of the Heidelberg Catechism on students' learning interest. PAK Teacher Leadership is a teacher who fears God, understands the truth of God's word, teaches based on God's word, carries out his duties and responsibilities as a teacher, leader and becomes an example for his students. Meanwhile, students' interest in learning is a desire within a person and a desire from outside that can foster a person's interest in learning. Based on the research results, it shows that the role of Religious Education Teachers as a leadership role is very important in increasing students' interest in learning and the level of Religious Education Teachers' role as leadership towards students' interest in learning.